Zur Definition des Begriffes Sozialbrache - Ruppert, Karl (ERDKUNDE, 1958)
Changes in the extent of agricultural land have frequently attracted the interest of geographers, and the appreciable number of investigations deserted settlements of the Middle Ages are well known. Whilst the term desertion has, however, mostly been linked up with periods of crises, and in particular population decline, a reduction in land used for agriculture is taking place here and there before our very eyes, despite population increase and a rise in the standard of living and despite the fact that in Western Germany the influx of expellees and refugees with an agricultural background would cause one to expect the very opposite development. Since this process, which is largely of a transitional character, is first of all due to social conditions, W. Hartke has coined the term Sozial brache (social fallow) to describe it. The whole host of problems connected with this phenomenon has in the meantime been investigated by many agricultural scientists, in particular agricultural economists. In accounts of the changes in the agricultural structure in Western Germany the term has frequently been used to express different things, the subject of the Sozialbrache phenomenon being topical. It seems, therefore, necessary to clarify the meaning of this concept. Besides a review of the different interpretations of the concept Sozialbrache, this paper presents an overall account of the most important publications on this topic, gives an indication of the distribution of Soizialbrache in Bavaria, and supplements the bibliography which was given in this journal by W. Hartke in 1956. Finally the concept Sozialbrache is defined as follows: Sozialbrache should be used to describe former agricultural areas now left fallow due to social differentiation. The latter is the result of the interaction of very varied complexes of factors, and is the decisive stage within an effective causal chain. The phenomenon of Sozialbrache is accompanied by a genuine or seeming rise in the standard of living of the people who formerly worked the land concerned and it is not at all due to a population decrease.